2014
DOI: 10.1111/avsc.12119
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity and grazing intensity in sub‐alpine and alpine grasslands inAndorra

Abstract: Questions Humans are altering land use and impacting grazing intensities worldwide in alpine and sub‐alpine grasslands, and functional diversity (FD) is a useful tool for predicting changes in these grassland communities and for improving biodiversity conservation. We asked: (1) how does functional richness (FRic) differ between the five predominant grassland types in Andorra (2) of these five grassland types, which plant communities are subject to high habitat filtering and which are driven primarily by compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…Those indices measure the effects of disturbance on functional biodiversity. For example, Komac et al [ 53 ] showed that grazing increases functional richness and functional dispersion in sub-alpine and alpine grasslands, which indicated that grazing was an essential mechanism in structuring these grasslands. In our study, functional richness was quantified using the multivariate FRic Index [ 12 ], in which all plant traits (n = 12) were categorical or ordinal variables ( Table 1 ); thus, functional richness was the number of unique trait combinations in the plant community [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Those indices measure the effects of disturbance on functional biodiversity. For example, Komac et al [ 53 ] showed that grazing increases functional richness and functional dispersion in sub-alpine and alpine grasslands, which indicated that grazing was an essential mechanism in structuring these grasslands. In our study, functional richness was quantified using the multivariate FRic Index [ 12 ], in which all plant traits (n = 12) were categorical or ordinal variables ( Table 1 ); thus, functional richness was the number of unique trait combinations in the plant community [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the functional analysis of grazing effects on the vegetation based on specific plant traits has become a "hot topic" (Kechang, He, Zhang, & Lechowicz, 2015;Komac, Pladevall, Domènech, & Fanlo, 2015;Teuber, Hölzel, & Fraser, 2013). The traitbased functional diversity approach can reveal the functioning of the ecosystem and mechanisms beyond the changes of taxonomic diversity and composition; thus, helping to explain dynamic changes in ecosystems (Carmona, Mason, Azcárate, & Peco, 2015;Villéger, Mason, & Mouillot, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the analyses of species diversity and composition, functional trait‐based approaches became increasingly involved in analysing and explaining the effects of grazing in grassland ecosystems (Teuber et al, ; Kechang et al, ; Komac et al, ). Trait‐based functional approaches can help to reveal the underlying mechanisms and support to sustain diversity and related ecosystem functions (Villéger et al, , Carmona et al, ).…”
Section: Introductionmentioning
confidence: 99%